The use of different packaging material on quality of shrimp (acetes erythraeus) nugget stored in cold temperature - Siti Masitah; Desmelati '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the effect of different packagingmaterials on quality of shrimp nugget stored in cold temperature (-18°C). Threeshrimp nuggets were prepared from a mixture of shrimp (72%), tapioca flour(14%), egg (9%), sugar (1%), salt (0,4%), pepper (1%) and garlic (2,6%). Thenuggets then were packaged respectively in without packed, in plastic bag at LowDensity Poly Ethylene (LDPE), High Density Poly Ethylene (HDPE) andPolypropylene (PP) and stored at cold temperature for 60 days. The nuggets wereevaluated for sensory quality, moisture, protein, total volatile base and totalpsychrophilic count at 0, 15, 30, 45 and 60 days of storage. The result showed thatthe nuggets packed in HDPE and PP had a longer storage life than that packed inLDPE and their quality were still acceptable up to 60 day storage. However,nugget packed in LDPE was rejected at 60 day storage. Moisture, protein, totalvolatile base and total psychrophilic count of the shrimp nugget stored in PP at 60day storage was 23,86%, 24,56%, 26,67 mg/100g, 7,4 x 104 sel/g respectively,HDPE was 23,12%, 22,74%, 30,40 mg/100g, 9,5 x 104 sel/g respectively andLDPE was 22,89%, 18,87%, 36% and 2,1 x 105 sel/g respectively.Keywords: Shrimp nugget, LDPE, HDPE, PP, cold storage